School-entry predictors of lower primary reading and mathematics achievement in Kenya. (11th September 2022) - Platas, Linda M; Perry, Lindsey; Piper, Benjamin; Sitabkhan, Yasmin; Ketterlin-Geller, Leanne
Using a longitudinal data set, this paper examines to what extent school-entry ( N = 553; mean age 6.32 years) early mathematics and literacy skills predict students' later achievement in a lower-middle-income country, Kenya. Controlling for socioeconomic status, intervention status, rural versus urban settings and parental literacy, the findings reveal that school-entry mathematics skills were significantly predictive of students' end of Grade 2 mathematics and reading achievement in English and Kiswahili. Likewise, school-entry English early literacy skills predicted students' end of Grade 2 mathematics and reading achievement in English and Kiswahili. This article extends earlier research on links between elements of school readiness and later achievement in high-income countries.